An introduction to marine biogeochemistry - Libes, Susan M. (John Wiley & Sons, 1992)
This book is divided into six parts: The physical chemistry of seawater; The redox chemistry of seawater; The chemistry of marine sediments; Organic biogeochemistry; Isotope geochemistry; and Marine pollution.